2017
DOI: 10.4081/ijfs.2017.6939
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of four essential oils against pigmenting Pseudomonas fluorescens and biofilmproducing Staphylococcus aureus of dairy origin

Abstract: Essential oils (EOs) are mixtures of secondary metabolites of plant origin with many useful properties, among which the antimicrobial activity is also of interest for the food industry. EOs can exert their antimicrobial potential both directly, in food products and active packaging, and indirectly, as sanitizing and anti-biofilm agents of food facility surfaces. Aim of this research was to evaluate the antimicrobial activity of four EOs (bergamot, cinnamon, manuka and thyme) against Pseudomonas fluorescens and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Recently, among the most promising strategies are natural compounds, including plant extracts, that can be easily used as additives in dairy food preservation. However, most compounds have been tested in vitro assays, mainly aimed at evaluating antimicrobial activity against both Pseudomonas spoilers and pathogens [168,169,170,171]. Based on the complexity of the food matrix, as well as intrinsic and extrinsic factors interfering with the activity of these compounds, the results obtained in vitro could not be confirmed in foods.…”
Section: Strategies To Control the Spread Of Antibiotic Resistant mentioning
confidence: 99%
“…Recently, among the most promising strategies are natural compounds, including plant extracts, that can be easily used as additives in dairy food preservation. However, most compounds have been tested in vitro assays, mainly aimed at evaluating antimicrobial activity against both Pseudomonas spoilers and pathogens [168,169,170,171]. Based on the complexity of the food matrix, as well as intrinsic and extrinsic factors interfering with the activity of these compounds, the results obtained in vitro could not be confirmed in foods.…”
Section: Strategies To Control the Spread Of Antibiotic Resistant mentioning
confidence: 99%
“…In ancient medical systems, microbial infection was treated mainly by herbal plant materials. A wide variety of antimicrobial agents are contained in plant-derived essential oils, such as eugenol in cloves, allicin in garlic and onion, cinnamic aldehyde in cinnamon, carvacrol in caraway, thymol in oregano, and menthol in thyme. Some essential oils have a wide application in the food industry as harmless flavoring substances and natural preservatives. , Thymol (2-isopropyl-5-methylphenol, Figure A), a common constituent of essential oils extracted from Thymus and Origanum plants, has antibacterial activity against a broad spectrum of microorganisms and can also improve the sensitivity of antibiotic-resistant microorganisms. Several in vitro studies have shown that thymol possesses bactericidal activity against S. aureus and methicillin-resistant strains. The antimicrobial activity of thymol is associated with the disruption of outer and inner membranes, which has been documented by the loss of membrane potential, cellular uptake of ethidium bromide, and leakage of potassium ions, ATP, and carboxyfluorescein. Thymol could enhance the bacterial susceptibility to tetracycline and benzalkonium by inhibiting the efflux pump . By inhibiting the transcription of EST2 and the telomerase activity, thymol could also accelerate telomere shortening in fungi .…”
Section: Introductionmentioning
confidence: 99%
“…Bergamot derivatives possess a high quantity of bioactive components including phenolics, flavonoids and other antioxidant compounds (Russo et al ., 2016; Giuffrè et al ., 2019) which throw light on their possible use in food processing to improve functional and microbiological characteristics. Moreover, it was demonstrated by literature that essential oil and juice of bergamot (Fisher and Phillips, 2006; Pedonese et al ., 2017; Rossi et al ., 2018) reduced the pathogens microbial growth and limited the biofilm formation of bacteria strains and their motility. Thus, in this research governing liquids containing bergamot concentrated juice and calcium lactate were evaluated for the preservation of lacto-fermented mozzarella cheese in relation to microbiological, sensorial and chemical characteristics.…”
mentioning
confidence: 99%